Estrous behaviour and vulva score in captive female Malayan Tapir (Tapirus indicus) - Yawah, Donny; Rovie-Ryan, Jeffrine; Che-Amat, Azlan; Fong, Michelle Wai Cheng; Ithnin, Hartini; Ahmad, Mohd Adli; Jeoffry, Enos; Misnan, Madzlan; Abdul Hamid, Zaihamrezal; Hiew, Mark W.H. (Penerbit Universiti Sains Malaysia, 2025)
The ex-situ propagation of the Malayan tapir in Malaysia is an important conservation strategy to increase the population of this endangered species. However, the scarcity of reproductive physiology studies impedes potential conservation efforts. This study aimed to investigate the expression of estrus signs through observation of estrus behaviour and vulva score in captive Malayan tapirs. This study was conducted from January to April at the Sungai Dusun Wildlife Conservation Centre, Selangor, Malaysia. A total of five female Malayan tapirs aged between 3 to 18 years old were involved in this study. Two of the tapirs were kept with a male partner, while three others were kept individually. Closed-circuit television (CCTV) cameras with night vision and audio recording function connected to a digital video recorder were used to record the female activity from 1930 to 0730 hours. The recorded videos were evaluated for estrus behaviour such as vocalisation, flehmen response, urine spraying and excretion smelling. The vulva score (scale of 0 to 4) was determined based on the vulva size and the presence of discharge. The most common estrus behaviour observed in the female Malayan tapirs was vocalisation (81%), followed by flehmen response (10%), urine spraying (5%) and excretion smelling (4%). The paired females were observed to exhibit more estrus behaviours than the non-paired females. Vulva changes were observed in both groups with evidence of cyclic pattern with an average median length of 31.0 days (range of 28 days to 33 days). Mann-Whitney U test revealed significant difference between paired group and non-paired group for vocalisation and urine spraying. Meanwhile, Spearman’s rho test showed a strong positive correlation between vulva score and flehmen response and very strong positive correlation between vulva score and excretion smelling. This study provides important information for the establishment of future captive propagation programmes.